Notes on Amanita section Validae in Hainan Island, China - Huang, Ting; Su, Lin-Jie; Zeng, Nian-Kai; Lee, Serena M. L.; Lee, Su-See; Thi, Bee Kin; Zhang, Wen-Hao; Ma, Jing; Huang, Hong-Yan; Jiang, Shuai; Tang, Li-Ping (Frontiers in Microbiology, 2023)
Hainan is the second largest island of China with the most extensive and well-preserved tropical forests and is also the largest island of the Indo Burma Biodiversity Hotspot. It provides in situ conservation for the unique ecosystem of the island. Recent studies have shown that there are diverse fungal species in Hainan. In this study, 24 collections of the genus Amanita from Hainan have been studied based on morphology and molecular systematics. Five new species belonging to Amanita section Validae are described: A. cacaina, A. parvigrisea, A. pseudofritillaria, A. pseudosculpta, and A. yangii. And A. parvifritillaria is recorded for the first time in Hainan. It is also the first report of this fungus occurring, outside Yunnan province, China. Among the five new species, two are unique in this section because of appendiculate pileus margin and absence of an annulus. Based on these new findings, the diagnosis of the section Validae should be slightly modified to include a few species with appendiculate margin and lack of annulus.